Regulation of Proteolysis of the Stationary-Phase Sigma Factor RpoS - Zhou, Yanning (American Society for Microbiology, 1998)
RpoS, the stationary-phase sigma factor of Escherichia coli, is responsible for increased transcription of an array of genes when cells enter stationary phase and under certain stress conditions. RpoS is rapidly degraded during exponential phase and much more slowly during stationary phase; the resulting changes in RpoS accumulation play an important role in providing differential expression of RpoS-dependent gene expression. It has previously been shown that rapid degradation of RpoS during exponential growth depends on RssB (also called SprE and MviA), a protein with homology to the family of response regulators, and on the ClpXP protease. We find that RssB regulation of proteolysis does not extend to another ClpXP substrate, bacteriophage lambda O protein, suggesting that RssB acts on the specific substrate RpoS rather than on the protease. In addition, the activity of RpoS is down-regulated by RssB when degradation is blocked. In cells blocked for RpoS degradation by a mutation in clpP, cells devoid of RssB show a four- to fivefold-higher activity of an RpoS-dependent reporter fusion than cells overproducing RssB. Therefore, RssB allows specific environmental regulation of RpoS accumulation and may also modulate activity. The regulation of degradation provides an irreversible switch, while the regulation of activity may provide a second, presumably reversible level of control.